2022
DOI: 10.1111/jam.15565
|View full text |Cite
|
Sign up to set email alerts
|

Perillaldehyde mitigates virulence factors and biofilm formation of Pseudomonas aeruginosa clinical isolates, by acting on the quorum sensing mechanism in vitro

Abstract: Aim The incidence of biofilm linked catheter‐associated urinary tract infections is increasing worldwide and Pseudomonas aeruginosa is one of the major causes. Perillaldehyde (PLD): as a natural, widely used flavouring agent, has been reported to possess various pharmacological properties. We hypothesized that PLD can inhibit biofilm formation and virulence factor (VF) production by P. aeruginosa by hampering the quorum sensing (QS) system(s). Methods and Results Minimum inhibitory concentration (MIC) of PLD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Tanreqing injection, Yunnan Baiyao water extract and the alcohol extract of burdock leaf, which have been used in clinic disease treatment, have also been reported to reduce QS system activity, which ultimately inhibits the production of virulence factors such as elastase and pyocyanin, reduces bacterial motility, and prevents biofilm formation [46][47][48]. Furthermore, some compounds derived from traditional herbs, such as luteolin from various herbs, paonol from Moutan cortex, perillaldehyde from Perilla frutescens and falcarindiol from Notopterygium incisum, have been reported as QSIs [49][50][51]. Our previous study demonstrated that wogonin and Sennoside A separately derived from Chinese herbs of Agrimonia pilosa and R. palmatum L exhibit QSI activity by targeting the pqs and las systems, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Tanreqing injection, Yunnan Baiyao water extract and the alcohol extract of burdock leaf, which have been used in clinic disease treatment, have also been reported to reduce QS system activity, which ultimately inhibits the production of virulence factors such as elastase and pyocyanin, reduces bacterial motility, and prevents biofilm formation [46][47][48]. Furthermore, some compounds derived from traditional herbs, such as luteolin from various herbs, paonol from Moutan cortex, perillaldehyde from Perilla frutescens and falcarindiol from Notopterygium incisum, have been reported as QSIs [49][50][51]. Our previous study demonstrated that wogonin and Sennoside A separately derived from Chinese herbs of Agrimonia pilosa and R. palmatum L exhibit QSI activity by targeting the pqs and las systems, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It showed anti-virulence activity and repressed biofilm formation. Molecular mechanism studies showed that it can interact with PqsR protein [ 69 ].…”
Section: Inhibitors Of the Pqs Systemmentioning
confidence: 99%